Challenges of Explicit and Implicit Communication A Relevance-Theoretic Approach - Jodlowiec, Maria (Text - Meaning - Context: Cracow Studies in English Language, Literature and Culture, 2015)
Relevance Theory provides an original theoretical framework to capture the complex nature and intricacies of the processes underlying ostensive communication. The model has been in constant development for the last 30 years, and this study attempts to contribute to it by challenging free enrichment as an important explicature-generation procedure. The mechanisms underlying the recovery of explicitly and implicitly communicated meanings are explored in this book. They show that by approaching communication as a creative process, Relevance Theory offers a coherent explanation not only of communication in which what is conveyed is relatively straightforward and easy to identify, but also of cases in which what is communicated is partly precise and partly vague